MODEL OF POLICY INNOVATION IN WASTE MANAGEMENT IN PADANG CITY - Anggraini, Dewi; Asrinaldi, Asrinaldi; Zetra, Aidinil; Valentina, Tengku Rika (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
Waste management is one of the problems considered to be damaging to the environment and disturbing to human health. The increasing population, consumption patterns, and low public awareness of participation in management, coupled with political factors, are considered triggers for the failure of waste management. In an era where waste continues to accumulate and its environmental impact is increasingly felt, the government's role in developing innovative policies is vital. This research aims to explain and analyze policy innovations in waste management in Padang City. The theory used is Allan McConnell's theory of policy innovation success and failure. The method employed is qualitative, utilizing a case study. The results of the study show that there are several programs in waste management in Padang City, starting with Regional Regulation No. 21 of 2012 concerning Waste Management, the integrated waste management program (PERSATU), the distribution of floating nets in various rivers, recycling waste entering malls, reducing the use of plastic bags in malls, thematic eco-enzyme villages, RDF technology, maggot cultivation, One Community Unit, One Waste Bank, One Bentor for Each Urban Village, Civil servants saving in waste bank, and Padang Bagoro. However, of the many waste management programs, the Padang City Government has not been able to reduce the amount of waste from year to year, this condition is caused by the sub- optimal political support from local political parties and this condition is exacerbated by the culture and participation of the community which does not support waste management programs in Padang City.